Reduction of nitrogen loss in runoff from sloping farmland by a ridged biochar permeable reactive barrier with vegetated filter strips - Zhang, Yuhe; Gao, Jianshuang; Li, Qiang; Zhuang, Shunyao (Frontiers in Environmental Science, 2024)
Introduction: Eutrophication due to nitrogen (N) loss from sloping farmland has a high risk in the Three Gorges Reservoir. Biochar and vegetated filter strips (VFS) are used to control nutrient runoff and increase soil water-holding capacity, soil nutrient retention, and crop yield. However, surface biochar application has limited ability to control N loss, especially from sloping farmland.In this study, different widths of ridged biochar permeable reactive barrier (RB-PRB) with VFS were employed to intercept N loss in runoff from sloping farmland. Adsorption characteristics of biochar for nitrate and ammonium N were evaluated using isothermal and kinetic adsorption models before field experiments. N index values for ammonium (NH4 + ), nitrate (NO3 -), dissolved N (DTN), particulate N (PN), and total N (TN) lost through runoff were monitored from April 2019 to January 2020.Results: NO3 -and NH4 + sorption on biochar was predominantly physical adsorption with a maximum capacity of 4.51 and 4.12 mg• g -1 , respectively. During the research period, the dominant transportation pathway of N loss involved dissolved total N movement through subsurface flow, which accounted for 65.55% of the total loss. TN loss for CK was 1954 g• hm -2 , while RB-PRB and VFS decreased N loss from sloping farmland by 36.7%. The interception efficiency of RB-PRB was highest at 0.3 m width. VFS successfully intercepted particulate N and reduced it by 32.75%. In terms of soil nutrients, the RB-PRB and VFS interventions led to a substantial 41.69% increase in the TN content of the soil at a 0.4m width.The findings suggest that biochar has a favorable adsorption effect on NH4 + and NO3 -, an appropriate width of RB-PRB with VFS could effectively reduce nitrogen loss from sloping farmland. Simultaneously, it enhances the water and fertilizer retention capacity of sloping cropland soil; however, the long-term implications necessitate further validation.